2020
DOI: 10.1088/1757-899x/932/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid System Method of Industrialised Building System (IBS): A Review of Studies

Abstract: A new technology in construction has implemented Industrialised Building System (IBS) as an adoption of a new method. Till date, the reception of Industrialised Building System (IBS) has been effectively advancing by Construction Industry Development Board (CIDB). Several of exertions have been taken, for example tremendous of research financing, preparing, and building up standard and other showcasing plan. From previous writing and industry report, the appropriation of IBS was practiced gainful to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A study conducted by Mohamad & Zin (2019) found that knowledge has a significant positive impact on a business entity. Authority like CIDB has played its role (Azmin & Kassim, 2020) in providing relevant IBS expertise; one of it is via IBS Centre. Although various efforts by the governments and authorities were initiated to penetrate IBS knowledge into the construction industry, Mohamed et al (2018) found that the IBS players are still lacking of IBS knowledge.…”
Section: Ineffective Knowledge Transfer Issuementioning
confidence: 99%
“…A study conducted by Mohamad & Zin (2019) found that knowledge has a significant positive impact on a business entity. Authority like CIDB has played its role (Azmin & Kassim, 2020) in providing relevant IBS expertise; one of it is via IBS Centre. Although various efforts by the governments and authorities were initiated to penetrate IBS knowledge into the construction industry, Mohamed et al (2018) found that the IBS players are still lacking of IBS knowledge.…”
Section: Ineffective Knowledge Transfer Issuementioning
confidence: 99%
“…In Malaysia this technologically enhanced method is known as the Indutrialised Building System (IBS) [19]. Generally, IBS hybrid means a combination of two different elements as stated in Azmin and Umar [12]. The elements can be any types of things that can be mix or combine in order to form one rigid component.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid is also anything that is a mixture of two or more things in Cambridge Dictionaries [11], something that is a combination of two different things, so it has qualities relating to both of them. According to Azmin and Umar [12] hybrid is a combination of the same component from IBS and conventional in-situ method. For example, beam structure has been combined between IBS precast and cast in-situ.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, in this examination there will be another technique that start executes from 2017 by JKR as a pilot ventures called Hybrid System to be highlighted. What's more, to be made sense of whether this strategy can causes delay nor get it be known as an effective technique [9].…”
Section: Introductionmentioning
confidence: 99%